Friday, October 13, 2023

A combinatorial proof of the Newton identities

Let $T_1,\dots,T_n$ be indeterminates. For all $m\geq0$, denote by $S_m$ the $m$th elementary symmetric polynomial, given by \[ S_m = \sum_{i_1 \lt \dots \lt i_m} T_{i_1}\dots T_{i_m}. \] These are polynomials in $T_1,\dots, T_n$, and as their names suggest, these polynomials are symmetric, meaning that \[ S_m (T_{\sigma(1)},\dots,T_{\sigma(n)}) = S_m (T_1,\dots,T_n) \] for any permutation $\sigma$ of $\{1,\dots,n\}$. By definition, one has $S_0=1$ (there is exactly one family of integers, the empty one, and the empty product is equal to~$1$) and $S_m=0$ for $m>n$ (there are no families of integers $1\leq i_1\lt\dots\lt i_m\leq n$). A well-known theorem asserts that any symmetric polynomial in $T_1,\dots,T_n$ (with coefficients in a commutative ring $R$) can be written uniquely as a polynomial in $S_1,\dots,S_n$ (with coefficients in $R$). It is in particular the case for the Newton polynomials, defined for $p\geq 0$ by \[ N_p = T_1^p + \dots+T_n^p . \] In particular, $N_0=n$ and $N_1=S_1$. The next Newton polynomial can be computed by “completing the square”: \[ N_2 = T_1^2+\dots+T_n^2 = (T_1+\dots+T_n)^2 - 2 S _1 = S_1^2 - 2S_1. \] These are the first two (or three) of a family of relations, called the Newton identities, that relate the polynomials $N_p$ and the polynomials $S_m$: \[  \sum_{m=0}^{p-1} (-1)^m N_{p-m}\cdot S_m + (-1)^p p \cdot S_p = 0. \] Using that the coefficient of $N_p$ is given by $S_0=1$, they allow to express inductively the polynomials $N_p$ in terms of $S_1,\dots,S_p$. If $p>n$, all terms with $m>n$ vanish. Using that the coefficient of $S_p$ is $N_0=p$, these formulas also show, conversely, that if $p!$ is invertible in the commutative ring $R$, then $S_1,\dots,S_p$ can be expressed in terms of $N_1,\dots,N_p$. There are various proofs of these identities. Most of the one I have seen are algebraic in nature, in so that they rely on the relations between the roots of a polynomial and its coefficients, and/or on expansion in power series. The following proof, due to Doron Zeilberger (1984) (Discrete Math. 49, p. 319, doi:10.1016/0012-365X(84)90171-7), is purely combinatorial. I have been made aware of it because it is the one that is formalized in the proof assistant system Lean. (See there for the source code.) We consider the set $S=\{1,\dots,n\}$ and define a set $X$ whose elements are the pairs $(A,k)$ satisfying the following properties:
  • $A$ is a subset of $S$;
  • $k$ is an element of $S$;
  • the cardinality of $A$ is less or equal than $p$;
  • if ${\mathop {\rm Card}}(A)=p$, then $k\in A$.
Define a map $f\colon X\to X$ by the following rule: for $(A,k)$ in $X$, set
  • $f(A,k) = (A \setminus\{k\}, k)$ if $k\in A$;
  • $f(A,k) = (A\cup\{k\}, k)$ if $k\notin A$.
Write $f(A,k)=(A',k)$; observe that this is again an element of $X$. The first two conditions are obvious. In the first case, when $k\in A$, then the cardinality of $A'$ is one less than the cardinality of $A$, hence is at most $p-1$, and the last condition is vacuous. In the second case, when $k\notin A$, the cardinality of $A$ is strictly smaller than $p$, because $(A,k)\in X$, so that the cardinality of $A'$ is at most $p$; moreover, $k\in A'$ hence the last condition holds. Observe that $f\colon X\to X$ is an involution: $f\circ f={\mathrm{id}}_X$. Indeed, with the same notation, one has $f(A,k)=(A',k)$. In the first case, $k\in A$, hence $k\notin A'$, so that $f(A',k)=(A'\cup\{k\},k)=(A,k)$; in the second case, one has $m\in A'$, hence $f(A',k)=(A'\setminus\{k\}, k)=(A,k)$ since $A'=A\cup\{k\}$ and $k\notin A$. Moreover, $f$ has no fixed point because it switches pairs $(A,k)$ such that $k\in A$ and pairs such that $k\notin A$. Zeilberger's proof of the Newton identities build on a function $w\colon X\to R[T_1,\dots,T_n]$ such that $w(f(A,k))=-f(A,k)$ for all $(A,k)\in X$. Since $f$ has no fixed point, the expression vanishes \[ \sum_{(A,k)\in X} w(A,k) \] since one can cancel a term $(A,k)$ with its image $f(A,k)$. Zeilberger's definition of the function $w$ is \[ w(A,k) = (-1)^{\mathrm{Card}(A)} T_k^{p-\mathrm{Card}(A)}\cdot \prod_{a\in A} T_a. \] It satisfies the desired relation: for $(A,k)\in X$ such that $k\notin A$, one has $f(A,k)=(A\cup\{k\}, k)$, so that \[ w(f(A,k)) = (-1)^{\mathrm{Card}(A)+1} T_k^{k-\mathrm{Card}(A)-1} \prod_{a\in A\cup\{k\}} T_a = - (-1)^{\mathrm{Card}(A)} T_k^{k-\mathrm{Card}(A)} \prod_{a\in A} T_a = w(A,k). \] When $k\in A$, one has $f(A,k)=(A',k)$ with $k\notin A'$, and the formula applied to $(A',k)$ implies the one for $(A,k)$, because $f$ is an involution. Now, in the relation $ \sum_{(A,k)} w(A,k) =0$, we first sum on $A$ and then on $k$: \[ \sum_{A\subset S} \sum_{k | (A,k) \in X} (-1)^{\mathrm{Card}(A)} T_k^{p-{\mathrm{Card}(A)}} \prod_{a\in A} T_a = 0\] and put together all those sets $A$ which have the same cardinality, say, $m$. This gives \[ \sum_{m=0}^n (-1)^m \sum_{\mathrm{Card}(A)=m} \prod_{a\in A} T_a \cdot \sum_{k | (A,k)\in X} T_k^{p-m} = 0. \] Let us compute separately the contribution to the sum of each $m$. When $m\gt p$, no subset $A$ is authorized so that the corresponding sum is zero. On the opposite, when $m\lt p$, for any subset $A$ such that $\mathrm{Card}(A)=m$, all pairs $(A,k)$ belong to $X$, so that the inner sum is $N_{p-m}$, and the whole term is $(-1)^mS_m N_{p-m}$. Finally, when $m=p$, the only $k$ that appear in the inner sum are the elements of $A$, and the corresponding term is $\sum_{k\in A} T_k^0=\mathrm {Card}(A)=p$; this term contributes to $(-1)^p p S_p$.